Kepastian Hukum Atas Penyelesaian Sengketa Tanah Bekas Milik Adat (Sunda Wiwitan Adat Karuhun Urang) yang Diwariskan Secara Individu - Tuti Andriani; Anriz N. Halim; Nurwidiatmo N (Postgraduate of Jayabaya University, 2018)
A life habit of people who are there to customary land are in a group of people and their utilization is regulated by the leaders of the group, then the joint rights are called ulayat land or beshickking recht ulayat land in the Adat Karuhun Urang (AKUR) Sunda Wiwitan Cigugur customary community is not doing well. The Sunda Wiwitan Cigugur AKUR community faces the possibility of expanding capital which can rob them of their customary land. In addition, it is also known that communal land in the AKUR Sunda Wiwitan Cigugur community can be owned by individuals and can be sold to buyers who are not actually members of the Sunda Wiur community of Wiwitan Cigugur. The method used in this study is sociological normative legal research. For data analysis, it is used with normative juridical analysis method. The author draws conclusions legal certainty by alternative / non-litigation resolution in the event of a conflict or dispute must heed legal principles and must pay attention to the principle of prosperity then the principle of security order and humanitarian principles among the community with the issue of indigenous peoples sunda wiwitan customary land AKUR in Cigugur Kuningan district. The party uses land for the benefit of the government or foreign parties.